THE FORMATION OF CONSCIENCE IN THE CONTEXT OF GLOBALIZATION - Kumar, James (Asian Horizons, 2016)
Conscience is the ‘voice of God’ that demands obedience. It inspires us with the ways of the Lord, revealing the “Will of God” in a here and now situation. Most unfortunately, this ‘voice of God’ is often not heard, disobeyed and tampered to echo the voices of the forces of the world. Globalization, a context in which we are living, is a most influencing force with its negative ideologies of ‘profit alone’ that permeates into all walks of human life, orientation and moral decision. Craving for economic advantages, political power and worldly pleasures – the ‘voice of God’ go faint. While making moral decisions, it is the voice of the former than the latter which gets priority, often leading to violence in various forms. To counter this, one has to unlearn what is wrongly learnt to relearn the right life principles according to the ‘voice of God.’ This article is an effort to point out some of these areas which are to be unlearnt and also shows life principles that are to be inculcated in one’s life in order that the conscience is formed well, adheres to the voice of God sincerely.